The Impact of Ensemble Techniques on Software Maintenance Change Prediction: An Empirical Study - Hadeel Alsolai; Marc Roper (Applied Sciences, 2022)
Various prediction models have been proposed by researchers to predict the change-proneness of classes based on source code metrics. However, some of these models suffer from low prediction accuracy because datasets exhibit high dimensionality or imbalanced classes. Recent studies suggest that using ensembles to integrate several models, select features, or perform sampling has the potential to resolve issues in the datasets and improve the prediction accuracy. This study aims to empirically evaluate the effectiveness of the ensemble models, feature selection, and sampling techniques on predicting change-proneness using different metrics. We conduct an empirical study to compare the performance of four machine learning models (naive Bayes, support vector machines, k-nearest neighbors, and random forests) on seven datasets for predicting change-proneness. We use two types of feature selection (relief and Pearson’s correlation coefficient) and three types of ensemble sampling techniques, which integrate different types of sampling techniques (SMOTE, spread sub-sample, and randomize). The results of this study reveal that the ensemble feature selection and sampling techniques yield improved prediction accuracy over most of the investigated models, and using sampling techniques increased the prediction accuracy of all models. Random forests provide a significant improvement over other prediction models and obtained the highest value of the average of the area under curve in all scenarios. The proposed ensemble feature selection and sampling techniques, along with the ensemble model (random forests), were found beneficial in improving the prediction accuracy of change-proneness.